Food and agriculture model for Finland - Lauri Kettunen (Agricultural and Food Science, 1980)
The purpose of the project of the Finnish food model is a) to examine what are the long term problems of Finnish agriculture b) to build a mathematical model which can be used for the description of the development of agriculture and which includes policy factors which affect the development, and c) to study what kind of policy actions are needed to secure selfsufficiency of agriculture in the long run. The first version of the model is presented in this article. It is a recursive simulation model where only the use of fertilizer is determined by optimization methods. The base year is 1978 and the development of agriculture can be simulated 25 years ahead. The estimates of parameters are mainly obtained from previous studies, but in some cases subjective consideration is needed